Folk poetry of Southern Leyte a collection of secular and religious folk poetry - Saga, Placida Go (University of the Philippines Press, 2010)
This book is a pioneering work on the folk poetry of Southern Leyte. It is not merely a collection of literary pieces; it also provides an explication of each literary type. With 221riddles, 50 proverbs, 54 folk songs, 11 balitao, 11 kulilisi berso, 15 daygon with 14 musical scores for different tunes, and 3 street pageants, the book can be a useful resource and reference material for high school and college courses in Philippine literature in Southern Leyte or the region. These literary pieces, now forgotten by most people and unknown and strange to the present generation, reveal the richness of Philippine culture. While it aims to create an awareness and revival of interest in the country's cultural heritage, this collection is hoped to enrich the content of the existing Philippine traditional literature.